2021
DOI: 10.1007/s11356-020-12036-9
|View full text |Cite
|
Sign up to set email alerts
|

Ozone potential to fight against SAR-COV-2 pandemic: facts and research needs

Abstract: The greatest challenge the world is facing today is to win the battle against COVID-19 pandemic as soon as possible. Until a vaccine is available, personal protection, social distancing, and disinfection are the main tools against SARS-CoV-2. Although it is quite infectious, the SARS-CoV-2 virus itself is an enveloped virus that is relatively fragile because its protective fatty layer is sensitive to heat, ultraviolet radiation, and certain chemicals. However, heat and liquid treatments can damage some materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 46 publications
(45 reference statements)
1
36
1
3
Order By: Relevance
“…Although few studies have investigated the relationship between ozone concentration and the microclimate conditions of different environments [88], some experiments have demonstrated that ozone concentration and relative humidity values played an important role in ozone efficiency and antimicrobial effect [89]. Humidity is an important parameter and must be considered because, in arid environmental conditions, the disinfection procedure may require a considerably longer exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies have investigated the relationship between ozone concentration and the microclimate conditions of different environments [88], some experiments have demonstrated that ozone concentration and relative humidity values played an important role in ozone efficiency and antimicrobial effect [89]. Humidity is an important parameter and must be considered because, in arid environmental conditions, the disinfection procedure may require a considerably longer exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…5,11 Ozon membunuh mikroba dalam waktu yang singkat dengan cara merusak dinding sel. 12,13 Ozon dengan konsentrasi 10 ppm efisien untuk membunuh virus dalam waktu 10 menit dalam ruangan kecil. 14 Penggunaan ozon dalam prosedur asepsis di klinik gigi khususnya di Indonesia, belum banyak dilakukan, mengingat ketersediaan alat penghasil gas ozon.…”
Section: Pendahuluanunclassified
“…20 Mikroba jamur mempunyai struktur polisakarida, lipid dan protein rantai panjang, lebih resisten terhadap efek oksidasi dari ozon. 13,27 Resistensi mikroba terhadap ozon diduga juga berhubungan dengan umur koloni.…”
Section: Pembahasanunclassified
“…Moreover, the virus-inactivating activity of ozone was demonstrated for different metals, contaminated with a corona pseudovirus and HuCoV-229E, such as stainless steel, nickel and copper as well as glass [ 19 ]. Since ozone dosages for disinfection of different surfaces vary, a process is needed that is suitable for hard materials and PPE [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%